Repurposing antimicrobials with ultrasound-triggered nanoscale systems for targeted biofilm drug delivery - Victor Choi; Dario Carugo; Eleanor Stride (npj Antimicrobials and Resistance)
Abstract Chronic infections represent a major clinical challenge due to the enhanced antimicrobial tolerance of biofilm-dwelling bacteria. To address this challenge, an ultrasound-responsive nanoscale drug delivery platform (nanodroplets) is presented in this work, loaded with four different antimicrobial agents, capable of simultaneous biofilm disruption and targeted antimicrobial delivery. When loaded, a robust protective effect against clinically-derived MRSA and ESBL Gram-positive and Gram-negative planktonic isolates was shown in vitro. Upon application of therapeutic ultrasound, an average 7.6-fold, 44.4-fold, and 25.5-fold reduction was observed in the antibiotic concentrations compared to free drug required to reach the MBC, MBEC and complete persister eradication levels, respectively. Nanodroplets substantially altered subcellular distribution of encapsulated antimicrobials, enhancing accumulation of antimicrobials by 11.1-fold within the biofilm-residing bacteria’s cytoplasm compared to treatment with unencapsulated drugs. These findings illustrate the potential of this multifunctional platform to overcome the critical penetration and localization limitations of antimicrobials within biofilms, opening potential new avenues in the treatment of chronic clinical infections.